2012
DOI: 10.1155/2012/782507
|View full text |Cite
|
Sign up to set email alerts
|

Severe Tetrodotoxin Poisoning after Consumption ofLagocephalus sceleratus(Pufferfish, Fugu) Fished in Mediterranean Sea, Treated with Cholinesterase Inhibitor

Abstract: Lagocephalus sceleratus, or better known as the pufferfish, or fugu, is widespread in Asia and Indo-Pacific regions. It is a poisonous fish containing tetrodotoxin (TTX) which is a potent neurotoxin. In the Far East, fugu is considered a delicate dish, especially in Japan where it is prepared by experts. Nevertheless, poisoning from Lagocephalus sceleratus is not a rare event. Recent data from Japan indicate an incidence of 45 patients per year and a mortality rate of 11%. Mediterranean sea is not the natural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 4 publications
0
32
0
1
Order By: Relevance
“…Despite this fact, the possibility for accidental consumption of these species is possible. Since 2007, when the first toxic European episode was reported in Málaga (Spain) by the consumption of trumpet shells of the species Charonia lampas lampas containing TTXs (Rodriguez et al, 2008), several episodes along the Mediterranean coastal countries have been reported due to the consumption of puffer fish (Bentur et al, 2008;Kheifets et al, 2012). Very recently the presence of TTXs has been reported in gastropods from Portugal (Silva et al, 2012) as well as in bivalve mollusk shellfish grown at the south coast of England (Turner et al, 2015), along the Greek coast (Vlamis et al, 2015) and in the Netherlands (RASFF, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Despite this fact, the possibility for accidental consumption of these species is possible. Since 2007, when the first toxic European episode was reported in Málaga (Spain) by the consumption of trumpet shells of the species Charonia lampas lampas containing TTXs (Rodriguez et al, 2008), several episodes along the Mediterranean coastal countries have been reported due to the consumption of puffer fish (Bentur et al, 2008;Kheifets et al, 2012). Very recently the presence of TTXs has been reported in gastropods from Portugal (Silva et al, 2012) as well as in bivalve mollusk shellfish grown at the south coast of England (Turner et al, 2015), along the Greek coast (Vlamis et al, 2015) and in the Netherlands (RASFF, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, a number of governmental initiatives have been launched to rapidly disseminate information about the risks posed by this toxic invader. This is, for instance, the case of Egypt, Turkey, Lebanon (Nader et al 2012), Cyprus, Greece, (Pancucci-Papadopoulou et al 2012), Tunisia (Ben Souissi et al 2014) and Spain, with the latter country being the most recent to document the occurrence of L. sceleratus in its waters . Raising awareness about the risks associated with the consumption of hazardous species is one of the key actions aimed at mitigating the impacts of unwanted invaders (Nader et al 2012) and to safeguard human health.…”
Section: Discussionmentioning
confidence: 99%
“…The need for the development of an EWCS is even more pressing due to the recent introduction of different marine toxic, venomous and poisonous alien species, which caused detrimental effects to human health, and even fatal intoxications in the most serious of cases Gweta et al 2008;Tichadou et al 2010 Prieto et al 2015;Tichadou et al 2010 and literature therein). Within the latter group, the most wellknown representative is the silver-cheeked toadfish Lagocephalus sceleratus (Gmelin, 1789) whose consumption by humans caused several cases of intoxication and even death, due to poisoning from tetrodotoxin (TTX) (see Kheifets et al 2012 and literature therein;Nader et al 2012). Based on the criteria used by the IUCN/GISP and endorsed by the SEBI2010 Working Group 5, the silver-cheeked toadfish is considered as one of the "worst" invaders of the Mediterranean Sea, exhibiting a welldocumented impact and/or possessing the potential to cause serious negative impacts on biological diversity and socio-economy (Streftaris and Zenetos 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A first toxic episode was described in 2007 in Málaga (Spain), caused by the consumption of trumpet shells caught in Portugal [16]. Afterwards, two episodes were reported along the Mediterranean coast, following the ingestion of L. sceleratus [17,18].…”
Section: Introductionmentioning
confidence: 99%